Dinamika Partisipasi Masyarakat dalam Proses Pembentukan Kitap Undang-Undang Hukum Pidana - Muhammad Afif (Supremasi Hukum: Jurnal Penelitian Hukum, 2024)
The Draft Criminal Code (RKUHP) has been approved by the People's Representative Council and the Government to become law. However, this ratification has left many problems in the formation process, one of which is in terms of community participation, which is considered to be minimal. This research departs from one key question: Has the community participation been implemented in the discussion process of the RKUHP until the draft is ratified in the DPR Plenary Session? The research method used is the normative juridical research method. The results show that there has been a neglect of community participation in the formation process, which caused the RKUHP to receive criticism and rejection. The government then responded by inviting those who disagreed to review the law to the Constitutional Court.